2012
DOI: 10.4236/ss.2012.310100
|View full text |Cite
|
Sign up to set email alerts
|

Single Incision Laparoscopic Surgery-An Overview and Current Status

Abstract: Single incision laproscopic surgery is an alternative to conventional multiport laproscopy. Natural orifice transluminal endoscopic surgery term coined by a Consortium in 2005 remains a research technique with few clinical cases. Single incision surgery offers advantage of better cosmesis, reduced incisions, lesser hernias, decreased pain and infections. Long learning curves and cost of instrumentation are the difficulties encountered in its propagation. Single incision laproscopic surgery is an evolving techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Three major factors that should influence the decision: the experience in CBD explora on the availability of endoscopic retrograde cholangiopancreatography, which the surgeon would use postopera vely, and the size of the stones, which indicates if they must be removed or are likely to come out on their own. The short hospital stay can be assumed to indicate the early resump on of normal ac vi es; three of the surgical groups reported that 6963 (85 percent) of 8192 pa ents who underwent LESC returned to full me employment within 7 23 days a er the surgery. The large number of laparoscopic cholecystectomies being performed within the frame work of this study suggests that LESC may be a more popular alterna ve to 3PLC surgery and 24 more than 4PLC.…”
Section: Discussionmentioning
confidence: 99%
“…Three major factors that should influence the decision: the experience in CBD explora on the availability of endoscopic retrograde cholangiopancreatography, which the surgeon would use postopera vely, and the size of the stones, which indicates if they must be removed or are likely to come out on their own. The short hospital stay can be assumed to indicate the early resump on of normal ac vi es; three of the surgical groups reported that 6963 (85 percent) of 8192 pa ents who underwent LESC returned to full me employment within 7 23 days a er the surgery. The large number of laparoscopic cholecystectomies being performed within the frame work of this study suggests that LESC may be a more popular alterna ve to 3PLC surgery and 24 more than 4PLC.…”
Section: Discussionmentioning
confidence: 99%